1981
DOI: 10.1088/0029-5515/21/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Lower hybrid heating in the Alcator A tokamak

Abstract: The results and interpretation of the modest nower ( 90 kW) lower hybrid heating experiment on Alcator A are presented.The expected results from linear waveguide-plasma coupling theory are outlined, and the possible effects of parametric instabilities, scattering from density fluctuations, and imperfect energetic ion confinement are addressed.It is found experimentally that good coupling and the absence of rf breakdown are achieved with a double wavecuide array 2 at available rf power densities Prf < 2.5 kW/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…In Ref. 6 it was shown that these minimum values for T7 and E,.Z were required by the slowing down of the tail ions on electrons. For a machine such as Alcator A, energetic ion orbit losses almost certainly affect this energetic ion distribution function.…”
Section: Introductionmentioning
confidence: 91%
“…In Ref. 6 it was shown that these minimum values for T7 and E,.Z were required by the slowing down of the tail ions on electrons. For a machine such as Alcator A, energetic ion orbit losses almost certainly affect this energetic ion distribution function.…”
Section: Introductionmentioning
confidence: 91%
“…The perpendicular wavenumber kl predicted by the cold plasma dispersion relation was too small for direct interaction between the LH and the beam ions. Without beam injection, many experiments have noted a direct correspondence between parametric decay of the fundamental LH wave and tail formation [158,166,167,171,172,241,2421. In these experiments, the tail develops at a lower density than that predicted for direct ion heating by LH waves (that obey the cold plasma dispersion relation).…”
Section: Lower Hybrid Wavesmentioning
confidence: 99%
“…Lower hybrid wave heating and current drive experiments are now being carried out at the I MW power level on the Alcator C tokamak to explore these issues. [1][2][3][4][5][6] Besides having successfully demonstrated current drive and electron heating, these experiments have shown the practicality of using large, multirow waveguide arrays to couple large RF power densities (P f/A -9 kW cm-2 ) into the tokamak plasma.…”
Section: Introductionmentioning
confidence: 99%